Is Risk Tolerance the Missing Link? Unpacking the Drivers of Investment Intention and Gender Differences Among Generation Z - Alfathya, Atmaya Fitra; Sumiati; Indrawati, Nur Khusniyah (Jurnal Aplikasi Manajemen, 2025)
The number of Single Investor Identification (SID) accounts is growing annually, primarily among Generation Z. However, a considerable disparity remains between those in this generation who have begun investing and those who have not. This situation warrants further examination to identify the factors that influence investment intentions among Generation Z in Malang. This explanatory study examines the effects of financial knowledge and social influence on investment intentions, considering the role of risk tolerance and gender differences. Utilizing purposive sampling, data from 224 Generation Z respondents in Malang were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that financial knowledge and social influence significantly impact investment intentions, with risk tolerance mediating this relationship. Partial Least Squares Multi-Group Analysis (PLS-MGA) reveals no significant gender differences. This study provides empirical evidence from Generation Z in Malang, showing that gender does not moderate the effects of financial knowledge and social influence on investment intentions. The findings offer practical implications for policymakers, educators, and financial institutions, highlighting the need for comprehensive financial education, building supportive social environments, and strengthening risk tolerance as key strategies to enhance Gen Z’s investment intention.